Downregulation of host tryptophan–aspartate containing coat (TACO) gene restricts the entry and survival of Leishmania donovani in human macrophage model - Gogulamudi, Venkateswara Reddy; Dubey, Mohan Lal; Kaul, Deepak; Atluri, Venkata Subba Rao; Sehgal, Rakesh (Frontiers in Microbiology, 2015)
Leishmania are obligate intracellular protozoan parasites of mammalian hosts. Promastigotes of Leishmania are internalized by macrophages and transformed into amastigotes in phagosomes, and replicate in phagolysosomes. Phagosomal maturation arrest is known to play a central role in the survival of pathogenic Leishmania within activated macrophages. Recently, tryptophan-aspartate containing coat (TACO) gene has been recognized as playing a crucial role in the survival of Mycobacterium tuberculosis within human macrophages by arresting the phagosome maturation process. We postulated that a similar association of TACO gene with phagosomes would prevent the vacuole from maturation in the case of Leishmania. In this study we attempted to define the effect of TACO gene downregulation on the uptake/survival of Leishmania donovani intracellularly, by treatment with Vitamin D3/Retinoic acid (RA) & Chenodeoxycholic acid (CDCA)/Retinoic acid (RA) combinations in human THP-1 macrophages (in vitro). Treatment with these molecules downregulated the TACO gene in macrophages, resulting in reduced parasite load and marked reduction of disease progression in L. donovani infected macrophages. Taken together, these results suggest that TACO gene downregulation may play a role in subverting macrophage machinery in establishing the L.donovani replicative niche inside the host. Our study is the first to highlight the importantrole of the TACO gene in Leishmania entry, and to identify TACO gene downregulation as potential drug target against leishmaniasis.